Microwave absorption study of dried banana leaves-based single-layer microwave absorber - Pattanayak, Soumya Sundar; Laskar, S. H.; Sahoo, Swagatadeb (International journal of microwave and wireless technologies, 2021)
The ever-increasing use of electronic devices leads to a dangerous upsurge in the emission of microwave radiation; this has drawn appreciable concern in the fabrication of eco-friendly microwave absorber (MA) and it can be a prospective alternative. Present work, in the quest for possible alternatives, explores carbon-rich agricultural residues such as dry banana leaves as a microwave-absorbing material. The variation of microwave absorption efficiency with an increase in the percentage of resin has been already reported. An extensive study on the microwave absorption efficiency of dried banana leaves with sample preparation and reflectivity analysis by hardware measurement, and simulative analysis using CST microwave studio suite for different thicknesses in the frequency range of 1–20 GHz has been also explored in the present work. Single-layer MA thickness variation establishes different microwave absorption performance.